3D PRINTING FOR THE FUTURE OF PHARMACEUTICALS DOSAGES FORMS - Bansal, Monisha; Sharma, Varun; Singh, Gurfateh; Harikumar, S. L. (International Journal of Applied Pharmaceutics, 2018)
With the rapid pace of development in industrial sector, the pharma sector and researchers involved are equally contributing in developing the latest technology for the growth and development. The computer-aided designs and manufacturing that provides 3 Dimensional printed dosage forms is the new step being taken into consideration. With the FDA approval to first 3D printed tablet in August 2015, Spritam, 3 Dimensional printing (3DP) has become the all new method for preparation of drug delivery system. 3D printing has the capability of dispensing the drug more accurately, precisely, and the layer by layer assembly helps in forming complex composition and geometries. 3D printing enables the preparation of personalised dosage form and tailored release profiles. 3D printing can be seen as future of solid dosage forms produced on demand, with customised dose and possibly lower in cost. It can help in reducing side effects caused by excessive doses. This review highlights the 3D printing technology and its applications in growth of pharmaceutical sector. An overview of reviews was conducted to locate published literature between 2000 and 2017.